Simulação realística na formação em enfermagem: percepção de docentes e discentes - Espadaro, Renato Fábio (2017)
The present study, titled Realistic Simulation in Nursing Training: teachers and students perception ", aimed at the perception of teachers and students about the efficacy of Realistic Simulation in nursing learning. The problem that stimulated this research was based on the following question: Does Realistic Simulation, as a method of teaching and learning in nursing, facilitate the work of teachers and students, especially in learning? In the search for an answer to this question, the research work began with the survey of theories of significant learning for adults and, in this universe, Paulo Freire was found as a theoretical reference for the research. The category of analysis chosen, in the Freirian legacy, to verify this model of learning was the "dialogue". Referring to methods and procedures, a bibliographical research was carried out to collect dialogue, teaching in nursing and Realistic Simulation. A qualitative and quantitative descriptive and exploratory field research was also carried out, building a profile of students and teachers, opinion research and semi-structured interviews. The results indicated that the majority of students and teachers understand that Realistic Simulation is a methodology that influences the quality of nursing learning, especially with respect to a consolidated training in safety and efficiency standards.